Analysis of printing parameters for tensile test using finite element analysis - Sukindar, Nor Aiman; Wan Abdul Hamid, Wan Luqman Hakim; Kamaruddin, Shafie (Springer, 2021)
D Printing technology has contributed a massive impact on various fields in parts fabrication. The flexibility in producing complex structure has placed this technology on high demand and understanding the technology is vital in achieving the desired outcome. Fused deposition modelling (FDM) is the most popular 3D printing technology, and it is widely used for different applications. However, this technology possesses some drawbacks which have opened the opportunity for some improvements. The present study is tackling the problem in improving the tensile strength of the FDM samples by using the finite element analysis (FEA). Several printing parameters were chosen, such as shell thickness, type of infill (lattice design), and lattice distance. The finding from this study concluded that the shell thickness contributes the most significant impact on the tensile strength, followed by the type of infill and lattice design. The optimum printing parameters were proposed as a guideline to improve the mechanical properties of the FDM printed parts.